THE EFFECT OF RADIOACTIVE RAYS ON THE HUMAN SENSORY SYSTEM (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
This article explores the damaging effects of ionizing radiation on the histological structure and function of the human sensory system, including vision, hearing, smell, taste, and tactile sensitivity. The discussion includes comparisons between normal histological features and radiation-induced changes such as degeneration, inflammation, and necrosis. Clinical manifestations, experimental findings on animal models, and pathological evidence highlight the high vulnerability of sensory tissues to radiation exposure. The material is intended for students and professionals in the fields of medicine, biology, and histology.